Improving Students' Understanding of Islamic Education Learning Using the Storytelling Method at SD Negeri 107828 Aras Panjang - Ridwan; Saragih, Paridah; Utari, Puspa (Journal of Indonesian Primary School, 2024)
This study aims to improve students' learning comprehension in Islamic religious education learning using the Storytelling Method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. The test is used to measure learning comprehension and observation is used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. the results of the study indicate that the Storytelling Method can improve students' learning comprehension in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, the use of the Storytelling Method can be used as an alternative to improve students' learning comprehension in Islamic religious education learning.